Non-Markovian memory in a measurement-based quantum computer - Filenga, D. [UNESP]; Mahlow, F. [UNESP]; Fanchini, F. F. [UNESP] (Amer Physical Soc, 2020)
We study the exact open system dynamics of one- and two-qubit gates during a measurement-based quantum computation considering non-Markovian environments. We obtain analytical solutions for the average gate fidelities and analyze them for amplitude damping and phase damping channels. We show, for both channels, that the average fidelity is identical for the X gate and Z gate and very similar for the pi/4 gate when considering the amplitude damping channel. Also, we show that fast application of the projective measurements does not necessarily imply high gate fidelity nor does slow application necessarily imply low gate fidelity. Indeed, for highly non-Markovian environments, it is of utmost importance to know the best time to perform the measurements, since a huge variation in the gate fidelity may occur given this scenario. Furthermore, we show that whereas for amplitude damping the knowledge of the dissipative map is sufficient to determine the best measurement times, i.e., the best times at which measures are taken, the same is not necessarily true for phase damping. For the latter, the time of the set of measures becomes crucial since a phase error in one qubit can fix the phase error that takes place in another. Finally, we show that these peculiar results disappear if all qubits are subjected to Markovian processes.